Mythopoeticisms in the epic poem Maulimniyaz-Edige - Iliasovna, Nurdauletova Bibaisha; Rezhepovish, Boranbaev Sandybai; Zhanat, Sultangalieva; Svetkalievna, Nurzhanova Aisara (Opción, 2020)
The article considers mythopoeticism in the epic poem Maulimniyaz-Edige via comparative qualitative research methods. As a result, if the epic poem is dated the 14th-15th centuries, it seems quite reasonable that the verbal arts of the people were used as the main tool for promoting religious ideas. In conclusion, a preliminary review of the study and systematization of the state of the mythological content of modern Kazakhstan prose shows that the process of convergence of literature with myth as one of the main forms of expanding its conceptuality, achieving philosophical depth is a complex aesthetic phenomenon requiring further detailed study.